Asperger's syndrome, the universe and everything - Hall, Kenneth, 1989- (Jessica Kingsley, 2001)
Kenneth Hall was diagnosed with Asperger Syndrome at the age of eight. He is in a unique position to describe some of the inner experiences and perceptions of autism in childhood. He has a warm and positive attitude to AS which other children will find inspiring. Insights, struggles and joys are recounted vividly in a frank and humorous way.